The Influence of Leadership Style, Employee Loyalty, and Work Motivation on Employee Performance at PT. Mitra Puding Mas Palm Oil Mill (PKS) - Diki Heryanto; Husaini Husaini; Ahmad Soleh (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study was motivated by the importance of improving employee performance as a key factor in achieving organizational goals at PT. Mitra Puding Mas’s palm oil mill. Employee performance is influenced by several internal factors, particularly leadership style, job loyalty, and work motivation. An effective leadership style can guide and influence employee behavior; job loyalty reflects commitment to the company; and work motivation serves as a driving force in improving productivity and work quality. This study aims to analyze the influence of leadership style, job loyalty, and work motivation on employee performance, both partially and simultaneously. The study employs a quantitative approach using a survey method via a questionnaire. Data analysis was conducted using multiple linear regression with the aid of SPSS, accompanied by validity and reliability tests, as well as hypothesis testing via t-tests and F-tests. The results of the study indicate that leadership style and work motivation have a positive and significant effect on employee performance, while job loyalty has a significant negative effect on employee performance. Collectively, leadership style, job loyalty, and work motivation have a significant effect on employee performance at PT. Mitra Puding Mas’s palm oil mill. These findings suggest that improving leadership style and work motivation can enhance employee performance, while job loyalty needs to be managed more effectively to contribute optimally to improved employee performance.